2018
DOI: 10.1038/s41598-018-27680-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bronchiectasis on outcomes of hospitalized patients with acute exacerbation of chronic obstructive pulmonary disease: A propensity matched analysis

Abstract: The coexistence of both Chronic Obstructive Pulmonary Disease (COPD) and bronchiectasis (BE) define an emerging phenotype with a worse prognosis; however, data about these patients do not consider baseline characteristics as confounders. We evaluate the impact of BE on outcomes of hospitalized patients with acute exacerbation of COPD (AECOPD). We prospectively considered AECOPD patients, analysed using a propensity score matching (PSM) method. The outcomes included length of hospital stay, use of non-invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
(66 reference statements)
1
20
1
2
Order By: Relevance
“…Of all of these, 14 duplicates were removed. After reviewing the titles and abstracts, 76 full-text articles were identified and reviewed, and, finally, 18 studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in this systematic review and meta-analysis. The flow diagram of article selection according to the PRISMA guideline 13 is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of all of these, 14 duplicates were removed. After reviewing the titles and abstracts, 76 full-text articles were identified and reviewed, and, finally, 18 studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in this systematic review and meta-analysis. The flow diagram of article selection according to the PRISMA guideline 13 is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 415,257 subjects with COPD from 18 observational studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were eligible for this meta-analysis, and bronchiectasis was present in 25,929 subjects (6.24%). The sample size ranged from 54 to 386,646, and 6 studies [17][18]20,22,25,33 had a small population (N < 100).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in the context of heart involvement during AECOPD, a recent study reported a significant negative role of intensive care unit admission or in-hospital mortality of pulmonary arterial enlargement defined by a pulmonary artery to aorta ratio >1 on chest computed tomography scan if associated with an increased troponin level (>0.01 ng/mL) [15]. Surprisingly, considering baseline characteristics as confounders using a propensity score matching method, the risk of death was similar in hospitalized AECOPD with and without bronchiectasis [16]. As for NIMV failure, non-invasive evaluation of DD at admission may also be a significant predictor of short-term mortality [9].…”
Section: Patients With a High Risk Of Short-term Mortalitymentioning
confidence: 99%